GREEN: MARKETING, PRODUCTS AND CONSUMERS - Raluca-Mihaela SANDU (SEA: Practical Application of Science, 2014)

(untitled)
The purpose of this paper is to provide a comprehensive literature review of green marketing, eco-friendly products and green consumers. Nowadays, awareness on different environmental problems increased significantly and it is of global concern to reduce negative impact on the environment. In relation to this, there has been a change in consumption patterns. As a result, a new segment of consumers was introduced, the so called green consumers. Green marketing tries to adapt by putting in the center of attention theneeds of such a consumer. An increase of organic products exists in both parts, in demand and offer. To maintain the welfare of present and future generations, a sustainable development is essentially.